2012
DOI: 10.5507/bp.2012.052
|View full text |Cite
|
Sign up to set email alerts
|

Rosiglitazone enhances neovascularization in diabetic rat ischemic hindlimb model

Abstract: Background. There is increasing evidence that peroxisome proliferator-activated receptors (PPARs) may be involved in the regulation of angiogenesis. In this study, we examined whether rosiglitazone, a PPARγ agonist, can restore angiogenesis in a rat hindlimb ischemia model of diabetes. Methods. Male wistar rats were divided into four groups (n=6 each): control, diabetic and control and diabetic rats who received rosiglitazone (8 mg/kg/day). Diabetes was induced by streptozotocin (55 mg/kg; ip). After 21 days, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Therapeutic angiogenesis and arteriogenesis remain an important goal in the case of patients with critical ischemia without revascularization possibilities. Many therapies have been attempted, with more or less encouraging effects [ 2 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therapeutic angiogenesis and arteriogenesis remain an important goal in the case of patients with critical ischemia without revascularization possibilities. Many therapies have been attempted, with more or less encouraging effects [ 2 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Capillary density (number of capillaries per number of muscle fibers) was determined in 10 different fields (magnification ×400), from each section from each animal, and was expressed as the mean number of CD31 positive cells per mm 2 . To avoid underestimation or overestimation of muscle density due to muscle atrophy or interstitial edema, the capillary/muscle fiber ratio was also expressed [ 17 ] (Khazaei and Salehi, 2012).…”
Section: Methodsmentioning
confidence: 99%
“…), VEGF‐C (Kuwahara et al . ) and rosiglitazone (Khazaei & Salehi ), which enhance capillary density and improve blood distribution after femoral artery ligation. Lu et al .…”
Section: Common Rodent Models Of Ischaemia or Non‐ischaemic Hypoperfumentioning
confidence: 99%
“…Ligation of the femoral artery leads, depending on the ligation site, to mild or severe ischaemia in the leg. Recently identified factors of therapeutic potential include prostacyclin (Aburakawa et al 2012), cilostazol (Biscetti et al 2012), VEGF-C (Kuwahara et al 2012) and rosiglitazone (Khazaei & Salehi 2012), which enhance capillary density and improve blood distribution after femoral artery ligation. Lu et al identified a new angiogenic factor AGGF1 (angiogenic factor with G patch and FHA domain-1), which triggers angiogenesis in this model (Lu et al 2012).…”
mentioning
confidence: 99%